2020
DOI: 10.1002/chem.201905577
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dithiasuccinoyl‐Caged Amines Enables COS/H2S Release Lacking Electrophilic Byproducts

Abstract: The enzymatic conversion of carbonyl sulfide (COS) to hydrogen sulfide (H2S) by carbonic anhydrase has been used to develop self‐immolating thiocarbamates as COS‐based H2S donors to further elucidate the impact of reactive sulfur species in biology. The high modularity of this approach has provided a library of COS‐based H2S donors that can be activated by specific stimuli. A common limitation, however, is that many such donors result in the formation of an electrophilic quinone methide byproduct during donor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…230 More recently, Pluth et al reported a suite of DTS-based compounds (donor 30, Figure 4P) that could be stimulated to produce COS/H 2 S by various nucleophiles such as cysteine, N-acetyl-L-cysteine (NAC), homocysteine, GSH, lysine but not serine, while lysine activated donor 30 through a pathway different from thiols-dependent one. 114 Similarly, S-methyl cysteine also gives rise to a slow but considerable H 2 S release, indicating a less preferred amino-dependent activation mechanism involved by lysine and S-methyl cysteine. 231 The experimental results that 25 μM of donor 30 could liberate ~40 μM H 2 S in the presence of 500 μM cysteine not only highlight the excellent H 2 S-releasing efficiency up to ~80% but also underpins the activation mechanism that two equivalents of COS were produced by per donor 30.…”
Section: Thiol-promoted H 2 S Releasementioning
confidence: 99%
“…230 More recently, Pluth et al reported a suite of DTS-based compounds (donor 30, Figure 4P) that could be stimulated to produce COS/H 2 S by various nucleophiles such as cysteine, N-acetyl-L-cysteine (NAC), homocysteine, GSH, lysine but not serine, while lysine activated donor 30 through a pathway different from thiols-dependent one. 114 Similarly, S-methyl cysteine also gives rise to a slow but considerable H 2 S release, indicating a less preferred amino-dependent activation mechanism involved by lysine and S-methyl cysteine. 231 The experimental results that 25 μM of donor 30 could liberate ~40 μM H 2 S in the presence of 500 μM cysteine not only highlight the excellent H 2 S-releasing efficiency up to ~80% but also underpins the activation mechanism that two equivalents of COS were produced by per donor 30.…”
Section: Thiol-promoted H 2 S Releasementioning
confidence: 99%
“…Alternatively, other approaches have utilized the intermediate release of carbonyl sulfide (COS), which is rapidly converted to H 2 S by the enzyme carbonic anhydrase (CA) (Figure a). , One common platform within this approach is the use of self-immolative thiocarbamates that can be triggered by specific stimuli to release COS. Moreover, these donor motifs provide access to critical control compounds, including triggerless control compounds and sulfur-depleted control compounds that release CO 2 rather than COS. Highlighting the diversity of this platform, prior donors have been developed that respond to both external and internal stimuli, including endogenous levels of peroxide, , bio-orthogonal chemistry, enzymes, , thiols, acid, nucleophiles, , and light. …”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of H 2 S donors have been designed over the past decade, [26–29] with several generating COS and relying on its CA‐mediated conversion into H 2 S [30–33] . Here we designed and synthesized a legumain‐responsive, COS‐releasing PHDC termed AAN ‐ PTC (Scheme 1; AAN represents the peptide component, and PTC represents the phenyl thionocarbonate).…”
Section: Resultsmentioning
confidence: 99%
“…A wide variety of H 2 S donors have been designed over the past decade, [26][27][28][29] with several generating COS and relying on its CA-mediated conversion into H 2 S. [30][31][32][33] Here we designed and synthesized a legumain-responsive, COSreleasing PHDC termed AAN-PTC (Scheme 1; AAN represents the peptide component, and PTC represents the phenyl thionocarbonate). The peptide component included the hexapeptide Ac-Glu-Glu-Phe-Ala-Ala-Asn (EEFAAN, Figure S1), where the EEF segment provided amphiphilicity and the AAN segment was the legumain-responsive epitope.…”
Section: Phdc Design and Synthesismentioning
confidence: 99%